The Agricultural Reform of 1981 and the Competition for Resources Between Peasant Farms and State-Owned Farms in the 1980s - Grala, Dariusz T. (Studia Historiae Oeconomicae, 2020)
In the economy of the Polish People’s Republic in the field of agriculture, the key resources which were a subject of competition included: land; production assets (machines, devices, tools for agricultural production, fertilizers, plant protection chemicals) and people necessary to work on farms and for farms. The command economy of the times of the People’s Republic of Poland was an example of an economy of permanent shortages, which increased in times of crises of the entire system. The collapse of 1979-1982 was such a socio-economic crisis. The Trade Union of Independent Farmers’ “Solidarity”, which was part of the great social protest movement in 1980-1981, forced a change in the communist regime’s approach to the peasantry and, together with other pressure groups, contributed to the implementation of the agricultural reform covering the entire sphere of agriculture and not only its state farm segment. The reform of 1981, initiated by the Rzeszów-Ustrzyki agreements, gradually changed the living situation of farmers and, above all, led to changes in the profitability of agricultural production and the legalization of trade in meat products at marketplaces as well as the release of prices for food products in 1989. Peasant farms won the competition with state-owned farms for capital resources – new production factors, and they expanded their land acreage (land factor). Farmers, however, were losing competition for workers in confrontation with industry and services in cities and state-owned farms, where farm workers could count on very generous social benefits.